2015
DOI: 10.1161/strokeaha.115.009854
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Bone Marrow Stem Cell Grafts Preferentially Migrate to Spleen and Abrogate Chronic Inflammation in Stroke

Abstract: Background and Purpose—Adult stem cell therapy is an experimental stroke treatment. Here, we assessed homing and anti-inflammatory effects of bone marrow stromal cells (hBMSCs) in chronic stroke.Methods—At 60 days post stroke, adult Sprague–Dawley rats received intravenous hBMSCs (4×106 labeled or nonlabeled cells) or vehicle (saline). A sham surgery group served as additional control. In vivo imaging was conducted between 1 hour and 11 days post transplantation, followed by histological examination.Results—La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(167 citation statements)
references
References 70 publications
3
163
0
Order By: Relevance
“…However, the researchers found that MSC homing to the spleen was important and correlated with a reduced infarct size and peri-infarct inflammation. They propose that MSCs exert a beneficial effect by abrogating secondary, inflammation-related cell death [130] . These data show that tissue-specific MSC homing is important, even though the target tissue is not the brain, as one would expect in a stroke model.…”
Section: Caveats In Modifying Homing Moleculesmentioning
confidence: 99%
“…However, the researchers found that MSC homing to the spleen was important and correlated with a reduced infarct size and peri-infarct inflammation. They propose that MSCs exert a beneficial effect by abrogating secondary, inflammation-related cell death [130] . These data show that tissue-specific MSC homing is important, even though the target tissue is not the brain, as one would expect in a stroke model.…”
Section: Caveats In Modifying Homing Moleculesmentioning
confidence: 99%
“…For example, Acosta et al transplanted MSCs at 30 days after stroke and found a therapeutic effect due to immunosuppression over the next 14 and 30 days [43]. How these MSCs were induced to be immunosuppressive during the chronic phase of stroke remains to be addressed too.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous and intra-arterial route of delivery has the disadvantage that majority of cells are grafted to other organs like lung, liver or spleen and only some cells are founded in the ischemic penumbra [49]. All these potential risk still need to be investigating in order to optimise stem cell therapy in stroke.…”
Section: Neural Progenitor Cell Therapy In the Post-acute Phase Of Stmentioning
confidence: 99%